International consensus on allergen immunotherapy II: mechanisms, standardization, and pharmacoeconomics - Jutel, Marek; Pfaar, Oliver (The journal of allergy and clinical immunology, 2016)
This article continues the comprehensive international consensus (ICON) statement on allergen immunotherapy (AIT). The initial article also recently appeared in the Journal. The conclusions below focus on key mechanisms of AIT-triggered tolerance, requirements in allergen standardization, AIT cost-effectiveness, and regulatory guidance. Potential barriers to and facilitators of the use of AIT are described in addition to future directions. International allergy specialists representing the European Academy of Allergy and Clinical Immunology; the American Academy of Allergy, Asthma & Immunology; the American College of Allergy, Asthma and Immunology; and the World Allergy Organization critically reviewed the existing literature and prepared this summary of recommendations for best AIT practice. The authors contributed equally and reached consensus on the statements presented herein.